MUSIC FROM MOZAMBIQUE, CHOPI TIMBILA. Two orchestral performances recorded in Zavala, Inhambane Province, Mozambique 1981, by Ron and Ophera Hallis. No. FE 4318, Folkways Records, 43 W 61st St. NYC, USA 10023. - Tracey, Andrew (International Library of African Music, 1987)
pages: 167-168
Keywords: Music; Performance; African Music; Mozambique; Orchestra